Does Pre-School Improve Child Development and Affect the Quality of Parent-Child Interaction? Evidence from Algeria - Moundir Lassassi (Global Labor Organization (GLO), 2020)
This paper investigates the impact of attending early childcare on the quality of parent–child interactions and children's cognitive outcomes. My identification strategy exploits geographical differences in terms of exposure to the program, controlling for the period when the program is implemented across Algerian municipalities as an instrument for individual early childcare attendance. I estimate 2SLS regression analysis and employ a difference-in-difference strategy. I use two Multiple Indicator Cluster Surveys conducted in 2006 and 2012. I find a positive effect of preschool on the cognitive development of children. In turn, the effect is only significant for mother with negative effect on the interaction between mother and children, which means that there is a substitution effect, mother use this time to do something else. These findings call for future research on parents', especially mother's, time use when their children attend early childcare.
Keywords: J13; H75; I20; I28; 330; Childcare; Cognitive skills; Family–child interaction; Time use; two stage least squares; Difference-in-difference